The Journey of Aeneas towards Western Mediterranean: a genealogy of the exiled hero’s myth - Mota, Thiago Eustáquio Araujo (Romanitas - Revista de Estudos Grecolatinos, 2021)
The condition of exiled and survivor is directly linked to Aeneas, the Trojan hero, son of Venus, who receives a prominent role in the foundational Roman narratives. This paper intends to track back the evidences concerning the construction of the traveler Aeneas in the pre-Virgilian written sources, in order to improve the understanding of the Aeneid itself.
Keywords: Aeneas; Travel Narrative; Myth; Aeneid; Mediterranean